FUNGSI PEMBERIAN IZIN USAHA INDUSTRI DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN DI ERA PEMBANGUNAN BERWAWASAN LINGKUNGAN - Rasdi Rasdi (Faculty of Law, Universitas Diponegoro, 2011)
Every businessman in the industry in conducting its business continuity capabilities required to maintain a harmonious environment and balanced to support sustainable development. This is more emphasized that any plan the establishment of industrial enterprises is estimated to have a significant impact on the environment must be accompanied Environmental Impact Assessment. The obligation is also a prerequisite for granting industrial enterprises, so that each business establishment industry is always bound to take action preservation capability environment to support environmentally sound development. Implementation of industrial licensing function as a means to control environmental pollution, as the negative impact of various business activities in the field of industry by supporting the principles of environmentally sound development that is being missed a lot of people.